PENGARUH IKATAN KEPENTINGAN KEUANGAN, FEE AUDIT, SIFAT MACHIAVELLIAN, DAN PEMAHAMAN ETIKA PADA INDEPENDENSI PENAMPILAN AUDITOR - Darmayanthi, Anak Agung Eka; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2017)
Independence in appearance means that accountants act impartially as perceived by users of financial statements. I ndependence of this appearance is determined by the public impression of the auditors themselves both individually and as a whole. This study aims to determine the effect of the financial interests of the bond, audit fee, Machiavellian nature and understanding of ethics on the independence of the auditor appearance. This research was conducted on a public accounting firm in the province of Bali listed on the Indonesian Institute of Accountants region of Bali 2015. S ampling method in this study was done by using the sampling nonprobability saturation sampling, in which all members of the population sampled. The results showed that the binding financial interests, audit fees, and the Machiavellian nature of the negative effect on the appearance of independence of the auditor. While understanding the ethics of positive effect on the appearance of the auditor's independence.
Keywords: : The Association of Financial Interests, Fee Audit, Machiavellian, Ethics, Independence Auditor Appearance